2016
DOI: 10.1007/s10658-016-0898-6
|View full text |Cite
|
Sign up to set email alerts
|

Damage thresholds and population dynamics of Pratylenchus penetrans on carrot (Daucus carota L. cv. Nerac) at three different seed densities

Abstract: Yield and quality loss of carrot (Daucus carota L. cv. Nerac) caused by Pratylenchus penetrans and the population dynamics of this nematode were studied in a climate controlled glasshouse. A range of 12 nematode densities was used at three different seed densities of carrot; 2, 4 and 18 seeds pot Pi/T-1 for Pi > T; y = 1 for Pi ≤ T for Tylenchina was fitted to the yield and quality loss data. Seinhorst's model for population dynamics of migratory nematodes with multiple generations; P f ¼ M *Pi= Pi þ M =a ð Þw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…The maximum multiplication rate (8813.2) obtained in this study is greater than previously reported values of M. incognita on pepper varieties (Di Vito et al, 1986, 1992Ferris et al, 1986;Abegaz, 2020) which might be due to difference in the host, pathogenicity, method of nematode extraction and duration or extracted time (Teklu et al, 2016).…”
Section: Population Dynamicscontrasting
confidence: 74%
“…The maximum multiplication rate (8813.2) obtained in this study is greater than previously reported values of M. incognita on pepper varieties (Di Vito et al, 1986, 1992Ferris et al, 1986;Abegaz, 2020) which might be due to difference in the host, pathogenicity, method of nematode extraction and duration or extracted time (Teklu et al, 2016).…”
Section: Population Dynamicscontrasting
confidence: 74%
“…The damage threshold for P. penetrans can vary a lot between vegetables. The damage thresholds for P. penetrans for faba bean and carrot were 6.2 (g soil) −1 and 1.37-1.88 (g dry soil) −1 , respectively (Seinhorst, 1998;Teklu et al, 2016). These numbers are equivalent to 868 and 192-263 P. penetrans (100 ml soil) −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Pratylenchus penetrans was multiplied on carrot discs (O'Bannon & Taylor, 1968) and in pots on maize (Teklu et al, 2016) to ensure sufficient nematode numbers for the experiments. The population was originally collected from maize roots in Kinrooi (Belgium) and had been maintained on carrot discs since 2006.…”
Section: Multiplication Of P Penetransmentioning
confidence: 99%
“…Nematodes must feed on plants to complete their life cycle, so planting two short-season crops such as pea or snap bean with a bare fallow mid-season can reduce reproduction. Damping the increase of P. penetrans decreases the need for aggressive measures such as fumigation in the potato year and increases the profitability of the targeted crop, as P. penetrans decreases yield of maize (MacGuidwin and Bender, 2016), soybean (Saikai and MacGuidwin, unpublished results), and carrot (Teklu et al, 2016). Verticillium dahliae has a more restrictive host range so new propagules of the fungus are not added during the rotation.…”
Section: Recommended Integrated Nematode Management (Inm)mentioning
confidence: 99%